Antimicrobial Susceptibility Test for the Determination of Resistant and Susceptible S. aureus and Enterococcus spp. Using a Multi-Channel Surface Plasmon Resonance Device - Ucak Ozkaya, Gulsum; Durak, Muhammed Zeki; Akyar, Isin; Karatuna, Onur (MDPI, 2019)
The objective of this study was to investigate the development of a surface plasmon resonance (SPR) sensor platform equipped with multiple channels for the simultaneous determination of methicillin-resistant S. aureus (MRSA), methicillin-susceptible S. aureus (MSSA) and vancomycin-resistant Enterococcus (VRE), and vancomycin-susceptible Enterococcus (VSE). Drug resistance of S. aureus strains against cefoxitin and Enterococcus strains against vancomycin were investigated both using the minimum inhibitory concentration method (MIC) assay and the SPR system equipped with single and multiple channels. The MIC values of MRSA and MSSA ranged from 32 mu g/mL to >128 mu g/mL and from 1 mu g/mL to 4 mu g/mL, respectively. The MIC values of VRE and VSE were between 64 to >128 mu g/mL and 2-4 mu g/mL, respectively. With the multiple-channel system, the angle shifts of MRSA, MSSA, VRE and VSE were found to be -0.030 degrees and -0.260 degrees, -0.010 degrees and -0.090 degrees respectively. The antibiotic-resistant and susceptible strains were distinguished within 3 h for S. aureus strains and within 6 h for Enterococcus strains.
Keywords: antimicrobial susceptibility; minimum inhibitory concentration assay; methicillin-resistant S. aureus; nosocomial infection; surface plasmon resonance; vancomycin-resistant Enterococcus; GRAM-POSITIVE COCCI; STAPHYLOCOCCUS-AUREUS; ANTIBACTERIAL; MECHANISMS; DISEASES; SPR; General & Internal Medicine